The dealmaker's ten commandments : ten essential tools for business forged in the trenches of Hollywood - Cohen, Jeff B. (Jeffrey Bertan), 1974- (Lanham ; [Chicago] : American Bar Association, 2015)
The Dealmaker's Ten Commandments provides a practical, no-nonsense methodology for negotiating deals, managing your time and handling crisis, all at the highest level. Authored by prominent transactional attorney and former child actor, Jeff B. Cohen, created The Dealmaker's Ten Commandments to overcome resistance and achieve his goals without losing his soul along the way. Although developed in Hollywood, the real world tactics, strategies and guiding principles are vital for any business environment.
Warning -- The dealmaker's methodology -- Chunk meets Machiavelli -- Dealmaker's commandment I : it is better to be feared than loved -- Dealmaker's commandment II : power leads, reason follows -- Dealmaker's commandment III : everyone is on the same side ... their own -- Dealmaker's commandment IV : things are precisely as they seem -- Dealmaker's commandment V : no pig wrestling -- Dealmaker's commandment VI : take yes for a yes, maybe for a yes, and no for maybe -- Dealmaker's commandment VII : do it, delete it, delegate it -- Dealmaker's commandment VIII : don't panic, stop the bleeding, don't compound the error -- Dealmaker's commandment IX : be a dealmaker, not a deal breaker -- Dealmaker's commandment X : heed Nietzsche's warning -- Curtain call.
Print version record.
Includes bibliographical references.
English.
eBooks on EBSCOhost
Keywords: Negotiation in business; Motion picture industry -- Law and legislation -- United States; Négociations (Affaires); BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Motion picture industry -- Law and legislation; Negotiation in business; United States